Reflective functioning and dissociative experiences: A comparison study between adolescents at “high-risk” of psychosis and healthy controls - Alberto Sardella; Alessandra Geraci; Vittorio Lenzo; Laura Fusar Poli; Alessandro Rodolico; Maria C. Quattropani; Maria Salvina Signorelli (Health Psychology Research)
# Background